1991
DOI: 10.1210/endo-129-2-959
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of μ- and κ-Opiate Receptor Control of the Hypothalamo-Pituitary-Adrenal Axis in Rats*

Abstract: The purpose of the present study was to determine the relative ontogeny of mu- and kappa-opiate receptor control of the hypothalamo-pituitary-adrenal (HPA) axis in rats. The ability of the mu-agonist morphine and the kappa-agonist U-50,488 to stimulate the HPA axis was determined by evaluating ACTH and corticosterone (CS) secretion in developing rat pups. Morphine elicited marked rises in both ACTH and CS secretion in 10-day-old rats, and these increases were maximal from 30-60 min after drug administration. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 46 publications
5
20
1
Order By: Relevance
“…The ACTH response to the nonopioid peptide fragment, Dyn A 2-17 , in combination with the lack of ACTH release in response to the highly selective ĸ-opioid receptor agonist, U50488H, is consistent with the involvement of nonopioid mechanisms. These findings are unlike previous findings in rats, showing that ĸ-opioid receptors may play a role in regulating the HPA axis [10, 11, 12]. This discrepancy suggests the involvement of opioid receptors in the regulation of the hypothalamic-pituitary axis, but not at the level of the pituitary.…”
Section: Discussioncontrasting
confidence: 99%
“…The ACTH response to the nonopioid peptide fragment, Dyn A 2-17 , in combination with the lack of ACTH release in response to the highly selective ĸ-opioid receptor agonist, U50488H, is consistent with the involvement of nonopioid mechanisms. These findings are unlike previous findings in rats, showing that ĸ-opioid receptors may play a role in regulating the HPA axis [10, 11, 12]. This discrepancy suggests the involvement of opioid receptors in the regulation of the hypothalamic-pituitary axis, but not at the level of the pituitary.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we have shown that an acute administration of morphine was able to induce a drastic and long-lasting pituitary±adrenal stimulation in 2-week-old newborns; by contrast, HPA axis activation was more transient and/or less robust in younger pups. ACTH and corticosterone release induced by morphine has been reported previously in 10-day-old rat pups (23). In agreement with our results, these authors reported that morphine-induced corticosterone release was lower on day 5 than on day 15 of postnatal life (23).…”
Section: Discussionsupporting
confidence: 94%
“…ACTH and corticosterone release induced by morphine has been reported previously in 10-day-old rat pups (23). In agreement with our results, these authors reported that morphine-induced corticosterone release was lower on day 5 than on day 15 of postnatal life (23).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Opioid peptides and their receptors are known to be involved in the regulation of the hypothalamic-pituitary-adrenal (HPA) axis, a major antistress system of mammals [9, 10, 11]. Especially, the POMC gene expressed in the anterior pituitary encodes both adrenocorticotropin (ACTH), a key regulator of the HPA axis, and β-endorphin, one of the endogenous µ-agonists.…”
Section: Introductionmentioning
confidence: 99%